Information frictions, belief updating and internal migration: Evidence from Ghana and Uganda - Sarah Frohnweiler; Bernd Beber; Cara Ebert (Journal of Development Economics, 2024)
Information frictions about benefits of migration can lead to inefficient migration choices. We study the effects of randomly assigned information treatments concerning regional income differentials in Ghana and Uganda to explore participants' belief updating and changes in internal migration intentions, destination preferences, and actual migration. Treated participants prefer higher income destinations, while effects on intent plausibly follow subjects' initial under- or overestimation of potential gains, with asymmetric updating propensities. Effects persist for 18 months, and discussions with others about migrating increase, but actual migration does not. Knowledge about income affects intentions and destination choices, but barriers to actual relocation are complex.
Keywords: J31; J68; O15; 330; Income differentials; Migration decision; Belief updating